Development of an educational interactive hardware‐in‐the‐loop missile guidance system simulator. Issue 2 (12th November 2017) - Chen, Zhongyuan; Chen, Wanchun; Liu, Xiaoming; Song, Chuang
Abstract: This paper presents a hardware‐in‐the‐loop (HIL) simulator, named HIL‐GSS, which aims to help the students of aerospace engineering learn control and missile guidance theories effectively by using interactive instrumentation. Electromechanical components and interactive panels are illustrated. Two case‐based studies are presented to show the advantages that HIL‐GSS offers to engineering education. Steady‐state tracking errors of the PID controller based on the HIL‐GSS are around zero. The final miss distance in the real‐time HIL TV guidance engagement simulation is 0.2376 m. Those results show the reliability of the proposed HIL simulator. In addition, the students' average response to survey questions is 4.22 (1–5 grade scale), which indicates that students strongly agree or agree that HIL‐GSS is an effective educational tool.